Decisão no ponto de equilíbrio econômico - uma análise do impacto do custo de oportunidade na formação de preços - Damasceno, Wellington Santos (2010)
This paper presents the concepts of Microeconomics and Marketing with the aim of complementing the work and discipline pricing. Expanding the vision strictly accounting for integrating concepts such as opportunity cost and price compost. This integration demonstrates the need for prices contain elements formed that reflect the economic sustainability of the company within a competitive context and considering the cost opportunity of equity invested. The inclusion these concepts changes the perspective of the results forcing the company to rethink and consider other aspects when pricing their products and services. Besides the exposure and integration between accounting concepts, economic and market proposed are simulations showing the impact of inclusion of these new approaches on the activity of pricing.